PERFORMANCES OF TIGER SHRIMP CULTURE IN ENVIRONMENTALLY FRIENDLY PONDS - Ahmad, Taufik; Tjaronge, M.; Suryati, E. (Indonesian Journal of Agricultural Science, 2003)
Mangrove ecosystem plays an obvious role in maintaining the biological balance in the coastal environment where shrimp ponds are usually constructed. The removal of mangroves around shrimp ponds has frequently brought about harvest failure. The study evaluated the performance of tiger shrimp culture in ponds provided with water from a water body where there was mangrove vegetation (hereafter mangrove reservoir). Twelve ponds, each measuring 2,500 m2, were filled with seawater from the mangrove reservoir until the water depth of 100 cm and then stocked with 20-40 PL/m2. In the first six ponds, the bottom water was released into the reservoir when the water depth reached 140 cm and then the water depth was maintained at 100 cm. In the second six ponds, the water was released from the ponds until the water depth reached 60 cm and then refilled with reservoir water until a depth of 100 cm. Both treatment ponds received water from the reservoir which also received the wastewater. The feeds for the shrimps were broadcast into the ponds twice a day to meet the 3% shrimp biomass requirement, which adjusted every other week through sampling. The result showed that mangroveÂ  vegetation is capable of removing excessive nutrients, up to 70% for NO3-N and NH4 +-N, reducing PO4 =-P fluctuation, and producing bioactiveÂ  compounds. In the second treatment ponds, shrimp mortality started to occur in day 28 and most died by day 54 after stocking due to white spot disease outbreak. Mass mortality took place 54 days after stocking in two out of six of the first treatment ponds.